El compromiso ambiental de la educación en ingeniería civil, con responsabilidad social (2021)
Professors of Tunja city should incorporate pedagogical strategies that allow to raise awareness on environment conservation. For this reason, the Universidad Santo Tomas will provide supportthrough an environmental conservation project, which include activities such as selection, classification and final disposal of solids wastes, organics and hazard solids as a way of the negative impact mitigation in the nature. This strategy will be developed through the cleaning of natural surface water streams, reforestation, workshops and video conferences, field trips and people sensibilization campaigns. The involvement of the Universidad Santo Tomas will contribute to the environment protection and the right use of the natural resources.